Тринадцатая редакция - Лукас Ольга (Тринадцатая редакция, 2011)
Экземпляры: ф.18 (20200616) / Инвентарный номер: 3450 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Л 84 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)6-445